Oral Care Program for Successful Long-Term Full Mouth Habilitation of Patients with Hypohidrotic Ectodermal Dysplasia - Yuan-Lynn Hsieh; Michael Razzoog; Sabrina Garcia Hammaker (Hindawi Limited, 2018)
Hypohidrotic ectodermal dysplasia (HED) is a rare congenital disorder that associates with dental manifestations of anodontia, hypodontia, and atrophic alveolar ridges. Although the disorder does not affect the life expectancy of the patient, it poses tremendous challenges on the patient's physical and psychosocial development. Early and multidisciplinary dental care can benefit HED children's development and improve their quality of life. This study presents two cases addressing the dental management continuously for 10 to 13 years in the dental school clinics. The keys to long-term success of the oral care program for HED patients at different age phases are reviewed and discussed, which can be summarized as early intervention, multidisciplinary collaborative care, and continuous recall.